MEDIA DAN TERORISME (Stereotype Pemberitaan Media Barat dalam Propaganda Anti-Terorisme oleh Pemerintah Amerika Serikat di Indonesia Tahun 2002) - Wijaya, Sri Herwindya Baskara (Jurnal The Messenger, 2010)
All year of 2002 in Indonesia, West media especially media in United States of America (USA) preference not balance to report issues about global terrorism from USA goverment. There are preference from part of media in West World which they see Islam via the news as believing violence and Islam peoples as source of global terroris wheares Islam as rahmatan lil alamin. This issues gives positive and negative effect for muslim in the world especially in Indonesia.